Comparative Analysis of Bioactive Compounds in Invasive and Native Land Snail Species of Java, Indonesia - Pertiwi, Meilisha Putri; Nurinsiyah, Ayu Savitri; Juliandi, Berry; Priawandiputra, Windra; Iskandar, Johan (Bogor Agricultural University, Indonesia, 2025)
Land snails are part of Indonesia's rich biodiversity. Their mucus is widely used as a natural ingredient in pharmaceuticals and cosmetics. Despite this, research has primarily focused on a limited range of species, leaving the potential of many native land snail species unexplored. This indicates that there is still significant untapped potential in native Indonesian land snail species. This research aims to analyze the bioactive compounds in the mucus of native Indonesian land snails and compare them with those of invasive species. The research employed Liquid Chromatography-Mass Spectrometry (LC-MS) to identify biologically active substances in land snail mucus. The samples used were Amphidromus palaceus and Lissachatina fulica collected from Gunungkelir, Yogyakarta, and Amphidromus perversus from Gunungkidul, Yogyakarta, and Jember, East Java. The results revealed that A. palaceus exhibited the highest number of bioactive compounds, with 28 identified substances. The bioactive properties across all samples were categorized as antibacterial (16%), wound healing and anti-inflammatory (12%), anticancer (8%), neuron-related drugs (6%), anti-aging (4%), with the remaining activities related to liver-related drugs, antiviral, heart disease-related drugs, and kidney disease-related drugs. These results highlight that native species have significant potential for further research, enabling their application in medicine and cosmetics.